Cholestatic Hepatocellular Injury with Azathioprine: A Case Report and Review of the Mechanisms of Hepatotoxicity - Joseph Romagnuolo; DC Sadowski; E Lalor; L Jewell; ABR Thomson (Canadian Journal of Gastroenterology)
Azathioprine is a drug commonly used for the treatment of inflammatory bowel disease, organ transplantation and various autoimmune diseases. Hepatotoxicity is a rare, but important complication of this drug. The cases reported to date can be grouped into three syndromes: hypersensitivity; idiosyncratic cholestatic reaction; and presumed endothelial cell injury with resultant raised portal pressures, veno-occlusive disease or peliosis hepatis. The components of azathioprine, 6-mercaptopurine and the imidazole group, may play different roles in the pathogenesis of hepatotoxicity. The strong association with male sex, and perhaps with human leukocyte antigen type, suggests a genetic predisposition of unknown type. Many of the symptoms of hepatotoxicity, such as nausea, abdominal pain and diarrhea, can be nonspecific and can be confused with a flare-up of inflammatory bowel disease. As well, the subtype resulting in portal hypertension can occur without biochemical abnormalities. A 63-year-old man with Crohn's disease who is presented developed the rare idiosyncratic form of azathioprine hepatotoxicity, but also had a severe disabling steroid myopathy, peripheral neuropathy, resultant deep venous thrombosis and pulmonary embolism related to immobility, and a nosocomial pneumonia. His jaundice and liver enzyme levels improved markedly on withdrawal of the drug, returning to almost normal in five weeks. Treating inflammatory bowel disease effectively while trying to limit iatrogenic disease is a continuous struggle. Understanding the risks of treatment is the first important step. There must be a low threshold for obtaining liver function tests, especially in men, and alertness to the need to discontinue the drug or perform a liver biopsy should patients on azathioprine develop liver biochemical abnormalities, unexplained hepatomegaly or signs of portal hypertension.